1997
DOI: 10.1055/s-2007-1004217
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Producing Color Change in Flat Early Gastric Cancers

Abstract: These results suggest that the main factor underlying color change in type IIb early gastric cancers may be the number of capillaries in the lesions, in comparison with the adjacent mucosa. Whether the lesion is visible on endoscopy, however, depends more on its size than on the number of capillaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 0 publications
1
52
0
Order By: Relevance
“…In the previous pathologic studies, the vascularity of gastric carcinoma within the mucosa was shown to differ according to the degree of the histologic differentiation (2,21,22). It was found that the mucosal vascularity of differentiated carcinoma compared with the surrounding non-cancerous mucosa was higher or about the same in most lesions, but lower in a few.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In the previous pathologic studies, the vascularity of gastric carcinoma within the mucosa was shown to differ according to the degree of the histologic differentiation (2,21,22). It was found that the mucosal vascularity of differentiated carcinoma compared with the surrounding non-cancerous mucosa was higher or about the same in most lesions, but lower in a few.…”
Section: Discussionmentioning
confidence: 95%
“…The intestinal-type gastric carcinoma has the same color or reddening when compared with the surrounding non-cancerous mucosa, whereas the diffuse-type gastric carcinoma is discolored and has a paler color compared with the surrounding mucosa (1). Some pathologic studies have suggested that these color changes seen endoscopically in intramucosal gastric carcinoma seemed to be correlated with the vascularity within the carcinomatous mucosa (2). The endoscopic color of early gastric carcinoma has usually been described as reddened, the same, discolored, or pale when compared with the color of the surrounding non-cancerous mucosa (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2a). On the other hand, FICE images with a set of wavelengths including 470 nm for blue (color gain level 4), 500 nm for green (5), and 550 nm for red (2) showed a flat and slightly brownish mucosal change, distinct from the surrounding yellowish area in the anterior wall (Fig. 2b).…”
Section: Case Reportmentioning
confidence: 99%
“…Current conventional endoscopy often misses flat early gastric cancers (0-IIb) because they are sometimes invisible [1,2]. Such flat gastric cancers have been detected by detailed histological examination of specimens resected by gastrectomy.…”
Section: Introductionmentioning
confidence: 99%